Feasibility, Acceptability, and Adherence with Short-Term HIV Preexposure Prophylaxis in Female Sexual Partners of Migrant Miners in Mozambique. (1st December 2017) - Lahuerta, Maria; Zerbe, Allison; Baggaley, Rachel; Falcao, Joana; Ahoua, Laurence; DiMattei, Pietro; Morales, Fernando; Ramiro, Isaias; El-Sadr, Wafaa M.
Abstract : Background: Preexposure prophylaxis (PrEP) offers protection from HIV acquisition if taken as prescribed. We evaluated the feasibility, acceptability, and adherence with short-term PrEP among female sexual partners of migrant miners in Mozambique. Methods: HIV-negative female sexual partners of migrant miners were offered daily tenofovir/emtricitabine (TDF/FTC) for 6 weeks concurrent with miners' return home. Study visits occurred at baseline, week 4, 6, and 8. Dried blood spots (DBSs) were collected at week 4 and 6. Results: Seventy-four women (median age: 42 years) were enrolled, 95% reported having 1 sexual partner and 80% reported never or rarely using condoms. At baseline, 41% had never tested for HIV; 65% were unaware of partners' HIV status. Of all women, 72 (97%) initiated PrEP, 7 (9%) discontinued PrEP before week 6; only 1 due to adverse events. Missed doses in the last week were self-reported by 8% and 3% of women at week 4 and 6, respectively. Of 66 (89%) women with DBS at week 4, 79% had detectable tenofovir diphosphate (TFV-DP) and 44% had levels consistent with ≥4 pills/wk (≥700 fmol/punch). Of 63 (88%) women with DBS at week 6, 76% had detectable TFV-DP and 42% had levels consistent with ≥4 pills/wk. Conclusions: In this first study assessing the use of short-term PrEP, a high percent of female partners of migrant workers initiated PrEP and had detectable DP levels during follow-up. Further efforts are needed to enhance adherence to ensure protection from HIV acquisition. Short-term PrEP offers promise for populations who are at high risk of HIV during specific periods of time.